In Vitro Effect of Estradiol and Progesterone on Ovine Amniotic Epithelial Cells - Annunziata Mauro; Hashimita Sanyal; Angelo Canciello; Paolo Berardinelli; Valentina Russo; Nicola Bernabò; Luca Valbonetti; Barbara Barboni (Stem Cells International)
Amniotic epithelial cells (AECs), an emerging source of extrafoetal stem cells, have recently attracted attention for their great regenerative potential. Since AEC amplifications are accompanied by the loss of their native epithelial phenotype and by the progressive reduction of relevant biological properties, the issue to be addressed is the development of effective culture protocols. In this context, recently, it has been demonstrated that progesterone (P4) supplementation during ovine AEC (oAEC) expansion could prevent the undesirable epithelial-mesenchymal transition (EMT). In contrast, there is no information to date on the role of the other pregnancy steroids in culture. With this aim, the present study has been designed to clarify the impact of estradiol (E2), alone or in combination with P4 (12.5 μM and 25 μM), during oAEC amplification. Steroid supplementations were assessed by testing oAEC proliferation, stemness, EMT, and osteogenic or chondrogenic plasticity. The results indicated that EMT can be prevented exclusively in the presence of high doses of P4, while it occurred rapidly in cells exposed to E2 as denoted by protein (cytokeratin-8 and alpha-SMA) and gene expression (vimentin and snail) profiles. Moreover, steroid exposure was able to influence highly oAEC plasticity. Particularly, P4-treated cells displayed a precommitment towards osteogenic lineage, confirmed by the upregulation of OCN, RUNX2, and the greater deposition of calcium nodules. Conversely, P4 exposure inhibited oAEC chondrogenic differentiation, which was induced in E2-treated cells as confirmed by the upregulation of chondrogenesis-related genes (SOX9, ACAN, and COL2A1) and by the accumulation of Alcian blue-positive extracellular matrix. Simultaneously, E2-treated cells remained unresponsive to osteogenic inductive stimuli. In conclusion, media supplementation with high doses of steroids may be adopted to modulate phenotype and plasticity during oAEC amplification. Relevantly, the osteo or chondro steroid-induced precommitment may open unprecedented cell-based therapies to face the unsolved orthopaedic issues related to osteochondral regeneration.